The nitrous oxide and methane emissions from Miscanthus x giganteus and Salix viminalis x schwerinii in Oakpark, Carlow, Ireland - Geoghegan, Sive (Trinity College (Dublin, Ireland). Department of Botany, 2012)
In investigating the reduction of the national greenhouse gas (GHG) footprint by replacing fossil fuels with bioenergy crops it is important to have a full GHG budget. We compared field emissions of nitrous oxide (N2O) and methane (CH4) for a Miscanthus x giganteus crop and a Salix viminalis x schwerinii (Tora) crop.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin.